Kees van der Heijden, a personal reflection: Commentary on Rowland and Spaniol 2021 - Lang, T (Wiley, 2021)
This piece is a personal reflection on the work and impact of Kees van der Heijden as part of the retrospective book review by Rowland and Spaniol (2021).